PERANAN KAPTEN H. SOERADI DALAM MENUMPAS PEMBERONTAKAN DI/TII JAWA TENGAH TAHUN 1955-1958 - Zainudin, Zainudin; Tugiman, Tugiman; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Captain Soeradi was one of the militay leaders of the Indonesian Police Department who officiates in a crushing the quelled of DI/TII Central Java 1955-1958. Captain Soeradi was born on March 14, 1935 from Pawirodirjo and Legiyem. The purpose of this research was found the biography of Captain Soeradi, found the role of captain Soeradi in the queledl rebellion of DI/TII of Central Java 1955-1958, found the activity of the Captain Soeradi after struggled in the quelled rrebellion of DI/TII of Central Java 1955-1958. The methods of this research was historical. Collected data and relics of the past and that hostory crirically to produced a scientific research. The historical methods used in this research are heuristics, criticism (history), interpretation, presentation. The result of this research was the role of Captain Soeradi as the team commander in the operation against the Central Java DI / TII rebellion which successfully crushed the rebellion against the Unitary State of the Republic of Indonesia. Captain Soeradi succeeded in devising a successful strategy to crush the Central Java DI / TII rebellion, and succeeded in attracting the sympathy of the public so as not to be influenced by DI / TII. After that, captain Soeradi was again assigned to the operation, namely the PRRI crackdown operation, Dwikora operation, and finally the PKI crackdown operation. When he retired, Captain Soeradi joined the Republic of Indonesia's Legion of Veterans organization in Riau Province.Key Words : DI/TII, Rebellion, The Role